Unilateral biportal endoscopic with modified arcocristectomy for pinching cervical spondylotic myelopathy: surgical technique and early experiences - Li, Xiaopeng; Hu, Haochen; Li, Penghe; Chen, Bing; Li, Feng; Chen, Chao; Xu, Baoshan; Ma, Xinlong; Cheng, Xigao; Yang, Qiang (Frontiers in Surgery, 2025)
ObjectivesIntroduce the surgical technique and early clinical efficacy of the modified arcocristectomy for treating pinching cervical spondylotic myelopathy using unilateral approach for bilateral decompression under cervical unilateral biportal endoscopy (UBE)surgery. This technique is being introduced for the first time and is applied for the first time in the treatment of pinching cervical spondylotic myelopathy.MethodsThis study enrolled nine patients with pinching cervical spondylotic myelopathy who underwent modified Arcocristectomy with UBE for unilateral approach and bilateral decompression at our medical center between December 2023 and November 2024. Patients' demographic data, imaging findings, and perioperative data were collected. Neurological recovery was assessed using the Japanese Orthopaedic Association (JOA) score and the Neck Disability Index (NDI). Imaging parameters, including cervical lordosis, segmental cervical angle at the surgical level, and maximum sagittal diameter of the spinal canal, were measured preoperatively, on the first postoperative day, and at the final follow-up. The safety and efficacy of the surgery were evaluated by comparing and analyzing these indicators.ResultsThe study included six men and three women, with an age range of 60–84 years (mean 70.75 ± 7.34 years). The mean preoperative symptom duration was 14.13 ± 16.57 months, and the mean follow-up duration was 14.00 ± 5.13 months. The mean preoperative Japanese Orthopaedic Association (JOA) score was 9.25 ± 3.28, which improved to 12.00 ± 3.21 on the first postoperative day, representing a mean improvement rate of 39.93 ± 15.07%. At the final follow-up, the mean JOA score was 14.38 ± 2.13, with a mean improvement rate of 69.85 ± 12.74%. The mean Neck Disability Index (NDI) score was 42.25 ± 15.00% preoperatively and decreased to 15.50 ± 5.90% at the final follow-up. Imaging results showed that the mean preoperative cervical lordosis was 19.04 ± 8.18°, which decreased to 4.91 ± 5.59° postoperatively and returned to 19.31 ± 7.82° at the final follow-up. The mean preoperative segmental cervical angle at the surgical level was 6.90 ± 3.82°, which decreased to 1.85 ± 2.08° postoperatively and returned to 7.05 ± 3.36° at the final follow-up. The mean preoperative maximum sagittal diameter of the spinal canal at the surgical level was 5.71 ± 2.03 mm, which increased to 11.98 ± 1.91 mm postoperatively. Intraoperatively, the mean anesthesia duration was 161.50 ± 47.11 min, and the mean surgical time was 108.13 ± 47.88 min. Blood loss was minimal. One patient experienced dizziness on the first postoperative day.ConclusionThe innovation of the modified Arcocristectomy surgery under cervical UBE for treating pinching cervical spondylotic myelopathy lies in the extended resection of the posterior-superior margin of the lamina. This modification effectively alleviates spinal cord compression caused by the “pinching effect” during cervical extension. Short-term follow-up results demonstrate significant clinical improvements, offering a new minimally invasive treatment option for this condition.